2016
DOI: 10.1111/ajt.13691
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing the Efficacy of Cyp3a5 Genotype‐Based With Body‐Weight‐Based Tacrolimus Dosing After Living Donor Kidney Transplantation

Abstract: Patients expressing the cytochrome P450 (CYP) 3A5 gene require a higher tacrolimus dose to achieve therapeutic exposure compared with nonexpressers. This randomized-controlled study investigated whether adaptation of the tacrolimus starting dose according to CYP3A5 genotype increases the proportion of kidney transplant recipients being within the target tacrolimus predose concentration range (10-15 ng/mL) at first steady-state. Two hundred forty living-donor, renal transplant recipients were assigned to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 32 publications
3
162
0
5
Order By: Relevance
“…The second trial, however, found no such advantage of CYP3A5-based dosing with 37.4% of patients receiving the standard bodyweight-based dose being within the Tac concentration range compared with 35.6% of the genotype-based group at first steady state. There was also no difference in the time to reach the target Tac concentration or the number of dose adjustments [98]. The explanation for this finding was that in the genotypebased arm, CYP3A5 non-expressers tended to have subtherapeutic concentrations more often after receiving the reduced starting dose.…”
Section: Pharmacogenetic Monitoringmentioning
confidence: 88%
See 1 more Smart Citation
“…The second trial, however, found no such advantage of CYP3A5-based dosing with 37.4% of patients receiving the standard bodyweight-based dose being within the Tac concentration range compared with 35.6% of the genotype-based group at first steady state. There was also no difference in the time to reach the target Tac concentration or the number of dose adjustments [98]. The explanation for this finding was that in the genotypebased arm, CYP3A5 non-expressers tended to have subtherapeutic concentrations more often after receiving the reduced starting dose.…”
Section: Pharmacogenetic Monitoringmentioning
confidence: 88%
“…In both trials, kidney transplant recipients were randomized to either receive the standard, bodyweight-based Tac dose (0.2 mg/kg/day) or to receive a dose customized to the CYP3A5 status of the patient (expressers 0.3 mg/kg/day and non-expressers 0.15 mg/kg/day) [98,99]. In the first study, genotype-based dosing resulted in significantly more patients being within the target Tac concentration range, 3 days after starting Tac (43.2%), compared with patients receiving the standard, bodyweight-based dose (29.1%).…”
Section: Pharmacogenetic Monitoringmentioning
confidence: 99%
“…[28] In a second RCT, 240 renal transplant recipients were randomized to receive a standard, bodyweight-based Tac starting dose (0.1 mg/kg twice daily) or a CYP3A5 genotype-based starting dose (0.075 or 0.15 mg/kg twice daily for CYP3A5 non-expressers and expressers, respectively). [29] Unlike the Tactique study, this trial only included recipients of a living kidney donor (who were genotyped for CYP3A5 during the workup for transplantation) and Tac was started on the day of transplantation rather than at day 7 post-transplant. All patients received basiliximab induction therapy and a standard MMF starting dose of 2 g/day followed by TDM.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…The majority of white patients (80% CYP3A5*3/*3) are initially overexposed with a standard tacrolimus loading dose (0.2 mg/ kg) (3)(4)(5). Because all tacrolimus concentrations (whether in the fixed-or adapted-dose group) are considered to be in steady state on day 10 (no dose changes allowed until then), the differences in PSL1 model performance in these subgroups (supplementary table 3 in Damon et al) cannot be explained by different dosing strategies, as the authors suggest (1).…”
Section: To the Editormentioning
confidence: 99%